Uses of Microorganisms in The Recovery of Oil and Gas - Ameen, Zena J. (Journal of Petroleum Research and Studies, 2024)
Microscopic organisms are the only single-celled organisms proposed for the advancement of techniques for Estimation of Oil Recovery (EOR) because they have numerous desirable properties, including a simple structure and an unsustainable growth rate when supplied with vital nutrients, resulting in the release of metabolic chemicals like Aerosols, acids, minimum lubricants, surfactants, and polymers. Clostridium acetobutylicum was isolated from intensive rice cultivation soil and has the ability to use polysaccharides such as starch and carboxylmethyl cellulose to produce biobutanol, while Desulfovibrio hydrocarbonoclasticus was isolated from marine sediment in Iraq and grows in anaerobic synthetic seawater medium with the addition of a trace element solution. These bacteria can also withstand difficult conditions High salinity, high pressure, and high temperature play roles and contribute to underground geological formations. An aqueous mixture of nutrients, Clostridium acetobutylicum, Desulfovibrio hydrocarbonoclasticus, and molasses with nutrient and bacterial spore injection into a reservoir. As a result, these microorganisms are capable of considerable catalytic reactions. production of a diverse spectrum of products (biosolvents, bioacids, biogases, and biosurfactants) from relatively simple nutritional compounds, multiply vigorously under favourable conditions, and have resulted in increased oil release from reservoir rock. The well began producing 70 days after the medication was started. 80 to 90 days after the injection began, relatively brief polyunsaturated fats, Carbon dioxide, and residues of ethanol, 1-butanol, and acetone were detected. Because of their highly resistant endospores, Clostridium are the most ideal of the several microbes used in MEOR (Microbial enhanced oil recovery). Desulfovibrio strains capable of producing biosurfactants in situ, which are beneficial to the MEOR process, are also valuable. Nutrients are often supplied as fermentable carbs to promote microbial metabolism.